2018
DOI: 10.1021/acs.cgd.8b01265
|View full text |Cite
|
Sign up to set email alerts
|

Old and New Insights into Structure and Properties of Eu2[SiO4]

Abstract: Lemon-yellow single crystals of Eu2[SiO4] were obtained by reaction of elemental europium with Eu2O3 in the presence of SiO2 carried out in evacuated silica ampules at 1373 K for 48 h followed by constant cooling to room temperature with 120 K per hour. Eu2[SiO4] crystallizes at room temperature in the larnite-type structure of β-Ca2[SiO4] (monoclinic, P21/n) with parameters a = 565.02(5), b = 709.15(6), c = 975.84(8) pm, β = 92.614(3)° for Z = 4. At 452 K it undergoes a reversible phase transition to an incom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…One possible position would be the Li3 site, which forms an octahedral coordination to two O 2− anions with Li–O distances of 205.0(2) pm and to four N 3− anions with Li–N distances between 218.9(2) and 248.94(5) pm resulting in a polyhedron size of 14.19 Å 3 . Although the distances are too short regarding typical Eu–O/N coordination (Eu–O distances range from 240 to 300 pm and Eu–N distances range from 260 to 325 pm), 49–51 local spatial distortion or enlargement of the octahedron could occur in contrast to the average structure. To maintain charge neutrality, the inclusion of a divalent Eu 2+ cation may be compensated by Li-vacancies in the surroundings or by local O/N substitution.…”
Section: Resultsmentioning
confidence: 99%
“…One possible position would be the Li3 site, which forms an octahedral coordination to two O 2− anions with Li–O distances of 205.0(2) pm and to four N 3− anions with Li–N distances between 218.9(2) and 248.94(5) pm resulting in a polyhedron size of 14.19 Å 3 . Although the distances are too short regarding typical Eu–O/N coordination (Eu–O distances range from 240 to 300 pm and Eu–N distances range from 260 to 325 pm), 49–51 local spatial distortion or enlargement of the octahedron could occur in contrast to the average structure. To maintain charge neutrality, the inclusion of a divalent Eu 2+ cation may be compensated by Li-vacancies in the surroundings or by local O/N substitution.…”
Section: Resultsmentioning
confidence: 99%
“…[ 43 ] Additionally, the yellow body color and emission of Li 2 Eu 3 Br 2 [BO 3 ] 2 also reminds of the optically similar europium(II) ortho ‐oxosilicate Eu 2 [SiO 4 ]. [ 40 ] As the luminescent properties of the latter have been subject to careful investigations by members of our group, similar studies are planned in collaboration with experts in this field for a future publication, since properties like emission maxima of bulk luminescence and the necessary theoretical considerations are beyond the scope of this article.…”
Section: Resultsmentioning
confidence: 99%
“…Actually, most of these phase transitions are reconstructive and occur at high temperatures (Felsche, 1973). However, there is also an example of a displacive phase transition, which was reported for Eu 2 SiO 4 (Busch et al, 1970;Funk et al, 2018). Eu 2 SiO 4 adopts monoclinic symmetry at room temperature and transforms to an orthorhombic structure at 438 K. Ananias and co-authors (2015) reported a lowtemperature phase transition in NaGd 0.99 Eu 0.01 SiO 4 .…”
Section: Introductionmentioning
confidence: 92%